Kawin Beda Agama dalam Kajian Hukum Islam dan Peraturan Perundang-Undangan di Indonesia - Sarifudin Sarifudin (Institut Agama Islam Negeri Curup, 2019)
This paper aims to reopen the discussion on the plurality of thoughts in interfaith marriages from the perspective of Islamic law and legislation in Indonesia. The method used is the literature study. Where the author tries to understand clearly the concept of interfaith marriage through books, documents and related research results. Whereas, in analyzing these data using the verstehen method. In this method, an interpretative analysis process is carried out on the concept of interfaith marriage. This interpretive analysis requires the writer to provide scientific arguments and criticisms in interpreting research data. In many cases in the community, interfaith marriages always create resistance. Religious arguments are always raised to oppose the marriage. One of the verses of the Koran which is popular for opposing interfaith marriages is QS al-Baqarah verse 221. But strangely, some people (muslims) continue to carry out interfaith marriages in the Civil Registry Office. The conclusion of this paper confirms that the legality of interfaith marriage is still debatable, both in Islamic law and regulations in Indonesia. Therefore, the new rules are needed that are clearer about interfaith marriages, because they are binding on each individual citizen, so that legal certainty and justice will be created.